Providing QoS for Networked Peers in Distributed Haptic Virtual Environments. (16th October 2008) - Marshall, Alan; Yap, Kian Meng; Yu, Wai
Abstract : Haptic information originates from a different human sense (touch), therefore the quality of service (QoS) required to support haptic traffic is significantly different from that used to support conventional real-time traffic such as voice or video. Each type of network impairment has different (and severe) impacts on the user's haptic experience. There has been no specific provision of QoS parameters for haptic interaction. Previous research into distributed haptic virtual environments (DHVEs) have concentrated on synchronization of positions (haptic device or virtual objects), and are based on client-server architectures. We present a new peer-to-peer DHVE architecture that further extends this to enable force interactions between two users whereby force data are sent to the remote peer in addition to positional information. The work presented involves both simulation and practical experimentation where multimodal data is transmitted over a QoS-enabled IP network. Both forms of experiment produce consistent results which show that the use of specific QoS classes for haptic traffic will reduce network delay and jitter, leading to improvements in users' haptic experiences with these types of applications.